Sentiment Analysis On The Presidential Threshold Policy In Elections As A Principle Of Democracy Jovi - Andreas, Jovianus Abel; Dazki, Erick (UNIVERSITAS PAKUAN, 2024)
Indonesia is a country that adheres to a presidential system of government. Elections are the basis of a democratic country in its implementation. Democracy is the government of reason by the people, for the people, and of the people, hence the people have the highest position in a democracy. The existence of a threshold is controversial in political dynamics because it is considered as a suppression of democratic values. Sentiment analysis is used to evaluate public assumptions about the application of the threshold by filling out a questionnaire that will be filled by subjects who have attitudes towards politics. Naïve Bayes and SVM are the methods used in solving sentiment analysis classification. Data collected through Twitter crawling is integrated with 1500 data from public assumptions about the presidential threshold. Naïve Bayes and SVM methods will be used to classify comment data. Through testing and classification, 784 comments were obtained which will be used as training data. The accuracy obtained from processing is 75.13% for Naïve Bayes and 83.29% for SVM.